Fe-NiCoSex / NCFF catalyst and preparation method thereof

Fe-NiCoSex/NCFF catalyst prepared by a one-step hydrothermal process uses nickel-cobalt iron-trimetal alloy foam to construct a catalyst rich in heterogeneous interfaces, solving the problem of insufficient stability of non-precious metal catalysts under high current density and achieving high efficiency Water cracking and stability are suitable for industrial applications.

CN119121301AActive Publication Date: 2024-12-13ZHEJIANG SCI-TECH UNIV

Patent Information

Application Number
CN202410978690.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2024-12-13
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

The existing non-precious metal catalysts that electrocatalyze water decomposition are insufficient in catalytic stability at high current density, making it difficult to meet the needs of industrial applications.

Method used

The Fe-NiCoSex/NCFF catalyst is prepared by a one-step hydrothermal process using a nickel-cobalt iron trimetal alloy foam to construct a catalyst rich in CoSe2-Ni3Se4 heterogeneous interface and uniformly doped with iron elements, combining micron-scale particles with crystal phase and amorphous phase structure.

Benefits of technology

It achieves efficient HER and OER at low overpotentials, and maintains stability of more than 20 hours at high current density, which is significantly better than the catalyst commonly used in laboratories and has industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121301A_ABST
    Figure CN119121301A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Fe-NiCoSex / NCFF catalyst, and relates to the technical field of catalysts, and the preparation method comprises the following steps: cleaning and drying NCFF foam; selenium powder, hydrazine hydrate and deionized water are mixed to be uniform, the NCFF foam is added, a reaction is conducted at a certain temperature, and the Fe-NiCoSe < x > / NCFF catalyst is prepared. The preparation method has the beneficial effects that nickel-cobalt-iron tri-metal alloy foam is selected, selenide nanoparticles are grown under a simple one-step hydrothermal process, the Fe-NiCoSex / NCFF catalyst which is rich in a CoSe2-Ni3Se4 heterogeneous interface, is uniformly doped with an iron element and is mixed with a crystalline phase and an amorphous phase is constructed, excellent HER and OER activities are shown, and the preparation method has the advantages that the preparation method is simple, the preparation cost is low, and the preparation method is suitable for industrial production. The catalyst is superior to most reported transition metal-based catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a Fe-NiCoSe x / NCFF catalyst and preparation method thereof. Background Art

[0002] In order to cope with challenges such as energy crisis and reduce environmental pollution, water splitting to produce hydrogen has become a common method. At present, the three most common ways to achieve hydrogen production by water splitting are based on electrocatalytic electrolysis, solid oxide electrolyzer (SOEC) and photoelectrochemical (PEC) electrolysis. Among these methods, electrocatalytic water splitting has attracted much attention due to its relatively environmentally friendly and economical characteristics. However, electrocatalytic water splitting includes two half reactions, the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). HER involves two electron transfers, while OER involves four electron transfers, which leads to slow kinetics, especially in alkaline media. Although precious metal-based materials (such as Pt, IrO 2 and RuO 2 ) are regarded as the leading electrocatalysts for HER and OER, but their scarcity and high cost limit their widespread application and commercialization. Therefore, the development of efficient non-precious metal electrocatalysts for alkaline HER and OER is of great promise but remains a huge challenge.

[0003] Recently, transition metal compounds have become the focus of extensive research due to their advantages such as low cost, multivalent states and suitable electronic structure, and are considered to be effective electrocatalysts for HER and OER. Among transition metal compounds, selenides (TMSes) have attracted extensive attention due to their good performance and excellent catalytic stability in HER and OER. It is reported that Ni grown on Ni substrates 3 Se 2 The nanostructures exhibited excellent catalytic activity and durability in both HER and OER. In addition, tests and DFT calculations found that NiSe 2 -FeSe 2 Multiphase heterogeneous structured nanosheets also show efficient overall hydrolysis performance and long-term stability. However, compared with precious metal-based catalysts, the activity of TMSes is still insufficient and there is a large gap between them and the industrial application requirements of high current density.

[0004] Constructing heterogeneous interfaces and designing element doping have always been effective ways to develop efficient bifunctional electrocatalysts. For example, the NiTe-NiSe heterostructure catalyst constructed by Wang 10 Both HER and OER show surprisingly high activity, requiring only low overpotentials of 76 mV and 164 mV, respectively. The multi-level structure Ni 2The P / (Co,Ni)OOH heterogeneous interface has high activity and stability in alkaline hydrogen evolution reaction. In addition, the doping of Fe has also been confirmed by Zhao's team to effectively improve the catalytic activity of NiSe nanowires. Sergio Battiato successfully promoted the oxygen evolution reaction by depositing iron-doped nickel oxide microflowers in a composition-controlled chemical bath. However, in order to adapt to the environment of industrial applications, in addition to high catalytic activity, catalytic stability at high current density is also extremely necessary. Therefore, it is urgent to develop non-precious metal-based bifunctional electrocatalysts that can maintain high catalytic activity at high current density. Summary of the invention

[0005] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a Fe-NiCoSe x / NCFF catalyst and its preparation method. The present invention proposes a new method with extremely simple process to prepare TMSes electrocatalyst, named Fe-NiCoSe x / NCFF, where x represents a mixture of various selenides with three metal components. The present invention uses nickel-cobalt-iron trimetallic alloy foam, in which the Fe content is only 0.5%, to grow selenide nanoparticles in an extremely simple one-step hydrothermal process to construct a CoSe-rich 2 -Ni 3 Se 4 Fe-NiCoSe with heterogeneous interface and uniformly doped iron, and mixed crystalline and amorphous phases x / NCFF catalyst. The electrochemical test confirmed its extremely high electrolytic water activity, which was mainly reflected in the low overpotentials of 36mV and 210mV, respectively. 10 The HER and OER processes can be realized at only 328 mV and 345 mV, respectively. 1000 , and can maintain high stability for 20 hours or more. Overall, compared with the commonly used j 10 and j 100 Activity test of Fe-NiCoSe x / NCFF in j 1000 DFT calculation results also prove that CoSe 2 (210)-Ni 3 Se 4 (202) The heterojunction has excellent electron density and reaction intermediate adsorption capacity, and exhibits its HER (-0.384 eV) and OER (ΔG 1st :0.243eV, ΔG 2nd :0.376eV) process requires an extremely low energy barrier.

[0006] The technical solution of the present invention is as follows:

[0007] A first aspect of the present invention provides a Fe-NiCoSe x / The preparation method of NCFF catalyst comprises the following steps:

[0008] Wash the NCFF foam and dry it;

[0009] Selenium powder, hydrazine hydrate and deionized water were mixed evenly, added to the NCFF foam, and reacted at a certain temperature to obtain Fe-NiCoSe x / NCFF catalyst.

[0010] Preferably, the NCFF foam cleaning method comprises: ultrasonically cleaning the NCFF foam in an acetone solvent and an HCl solution for 5 to 15 minutes respectively, and then taking out the NCFF and washing the surface with anhydrous ethanol and deionized water in turn.

[0011] Preferably, the NCFF foam drying method comprises: drying the cleaned NCFF in a drying oven at 45 to 55° C. for 10 to 20 minutes.

[0012] Preferably, the ratio of the selenium powder, hydrazine hydrate and deionized water is 0.06-0.1 g: 1.5-2.5 ml: 18-22 ml.

[0013] Preferably, the ratio of the selenium powder, hydrazine hydrate and deionized water is 0.07-0.09 g: 1.8-2.2 ml: 19-21 ml.

[0014] Preferably, the ratio of the selenium powder, hydrazine hydrate and deionized water is 0.08 g: 2 ml: 20 ml.

[0015] Preferably, the reaction is carried out in a forced air drying oven at 160-200° C. for 20-28 hours.

[0016] Preferably, the reaction is carried out in a forced air drying oven at 180° C. for 24 hours.

[0017] Preferably, the NCFF foam has a size of 0.5-1.5 cm×0.5-1.5 cm.

[0018] The second aspect of the present invention provides a Fe-NiCoSe prepared by the above-mentioned preparation method. x / NCFF catalyst. Among them, from the morphology, Ni, Co, Fe, Se and O elements are evenly distributed. From the content, Ni atomic content is 5.56%, Co atomic content is 36.51%, Fe atomic content is 0.78%, Se atomic content is 47.34% and O atomic content is 9.81%.

[0019] The present invention has at least one of the following beneficial effects:

[0020] The present invention uses nickel-cobalt-iron trimetallic alloy foam to grow selenide nanoparticles in a simple one-step hydrothermal process to construct a CoSe-rich 2 -Ni 3 Se 4 Fe-NiCoSe with heterogeneous interface and uniformly doped iron, and mixed crystalline and amorphous phases x / NCFF catalyst.

[0021] The Fe-NiCoSex / NCFF prepared by the present invention through a simple one-step process exhibits excellent HER and OER activities, which are superior to most reported transition metal-based catalysts. The catalyst has uniformly dense micron-sized selenide particles and dense nanowires on its surface, which provide it with a huge reaction surface area and abundant active sites, and has a large electrochemically active specific surface area. The incorporation of trace Fe elements allows the catalyst to grow into a richer selenide structure during the selenization process, and the nickel, cobalt and iron trimetallics constitute micron-sized particles that integrate crystalline phases and amorphous phases, greatly improving the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The Fe-NiCoSe x / Flow chart of the preparation process of NCFF catalyst.

[0023] Figure 2 It is a comparison chart of the HER (a) and OER (b) performances of the catalysts prepared in Examples 1 to 3.

[0024] Figure 3 It is a comparison chart of the HER (a) and OER (b) performances of the catalysts prepared in Examples 1 and 4-5.

[0025] Figure 4 It is a comparison chart of the HER (a) and OER (b) performances of the catalysts prepared in Examples 1 and 6-7.

[0026] Figures 5-6 It is the XRD spectrum of the catalyst prepared in Example 1 and Comparative Examples 1-2.

[0027] Figure 7 These are morphological images of the catalyst prepared in Example 1. a is a low-resolution morphological image, b is a high-resolution SEM image, c is a skeleton mapping image, d is a low-resolution TEM and elemental energy spectrum image, and e and f are high-resolution TEM images.

[0028] Figure 8 It is the XPS spectrum of the catalyst prepared in Example 1. a is the full XPS spectrum, and bf are the high-resolution spectra of each element.

[0029] Fig. 9 Figure 1 is a graph showing the electrocatalytic performance of the catalysts prepared in Example 1 and Comparative Examples 1 to 3 and the two substrates NCFF and NCF. a is the LSV curve, b is the Tafel slope data, c is the electrochemical impedance spectroscopy (EIS) Nyquist plot, d is the LSV curve of the sample after 10,000 cyclic voltammetry (CV) scans, and e is the j 10 , j 100 and j 1000 The chronoamperometric curve below.

[0030] Fig.10 SEM low-resolution and high-resolution images of the sample after It test of the catalyst prepared in Example 1. a is a low-resolution SEM image, and b is a high-resolution SEM image.

[0031] Fig.11 It is the crystal structure XRD spectrum of the catalyst It sample prepared in Example 1.

[0032] Fig.12 The performance test diagrams of the catalysts prepared in Example 1 and Comparative Examples 1 to 3 and the two substrates NCFF and NCF as OER working electrodes are shown in Figure 1. a is the LSV curve, b is the Tafel slope, c is the electrochemical impedance diagram, d is the LSV curve after 10,000 voltammetric cycle (CV) scans, and e is the constant voltage chronoamperometry curve.

[0033] Fig.13 The sample morphology of the catalyst prepared in Example 1 after OER reaction It test. a is a low-resolution scanning electron microscope image, and b is a high-resolution scanning electron microscope image.

[0034] Fig.14 This is the XRD spectrum of the catalyst prepared in Example 1 after OER reaction It testing.

[0035] Fig.15 The double layer capacitance current (Cdl) diagram of the catalyst prepared in Example 1 and Comparative Example 1. a~b are Fe-NiCoSe x / NCFF, c~d are NiCoSe x / NCF, e~f are NCFF.

[0036] Fig.16 is the CoSe of the catalyst prepared in Example 1 2 (210), Ni 3 Se 4 (202) and CoSe 2 (210)-Ni 3 Se 4 (202)Atomic model of heterojunction.

[0037] Fig.17 is the DOS diagram of the catalyst prepared in Example 1.

[0038] Fig.18 The CoSe in the HER of the catalyst prepared in Example 1 2 (210), Ni 3 Se 4 (202) and CoSe 2 (210)-Ni 3 Se 4 (202)Gibbs free energy evolution diagram of heterojunction.

[0039] Fig.19 The OER of the catalyst prepared in Example 1 is CoSe 2 (210), Ni 3 Se 4 (202) and CoSe 2 (210)-Ni 3 Se 4 (202) Gibbs free energy evolution diagram of heterojunction DETAILED DESCRIPTION

[0040] The present invention is achieved by Figure 1 The method shown in the figure successfully synthesized Fe-NiCoSe by using nickel-cobalt-iron trimetallic foam (NCFF) through a one-step hydrothermal selenization reaction. x / NCFF.

[0041] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0042] All chemical reagents used in the following examples were of analytical grade, and water was deionized water. 3 COCH 3 , AR, 99.5%), hydrochloric acid (HCl, AR, 36%) and anhydrous ethanol (CH 3 CH 2 OH, AR, 99.7%) was purchased from Hangzhou Shuanglin Chemical Reagent Co., Ltd. Hydrazine hydrate (N 2 H 4 H 2 O, AR, 50%) and potassium hydroxide (KOH, AR, 90%) were purchased from Shandong Xiya Chemical Industry Co., Ltd. Selenium powder (Se, AR, 99.9%), platinum carbon (Pt / C, AR, 20wt%), ruthenium oxide (RuO 2 , AR 99.9%) and perfluorosulfonic acid (Nafion) were purchased from Shanghai McLean Biochemical Technology Co., Ltd. Nickel-cobalt-iron alloy foam (NCFF) was purchased from Suzhou Taili Foam Factory.

[0043] Example 1

[0044] NCFF foam with a size of 1×1 cm was ultrasonically cleaned in acetone solvent and 1 mol / L HCl solution for 10 min respectively. After the NCFF was taken out, the surface was rinsed with anhydrous ethanol and deionized water three times in turn, and then dried in a drying oven at 50°C for 15 min to obtain pollution-free NCFF foam.

[0045] Add 20 ml of deionized water, 0.08 g of selenium powder and 2 ml of hydrazine hydrate into the inner tank of the reactor, mix well and add the cleaned NCFF foam, transfer the inner tank to the autoclave reactor, and react at 180° C. in a forced air drying oven for 24 h.

[0046] When the reactor cooled to room temperature, the sample was taken out and washed to obtain Fe-NiCoSe x / NCFF catalyst.

[0047] Example 2

[0048] The difference from Example 1 is that the amount of selenium powder added is changed to 0.06 g, and the rest is the same as Example 1.

[0049] Example 3

[0050] The difference from Example 1 is that the amount of selenium powder added is changed to 0.1 g, and the rest is the same as Example 1.

[0051] Example 4

[0052] The difference from Example 1 is that the reaction temperature is changed to 160° C., and the rest is the same as Example 1.

[0053] Example 5

[0054] The difference from Example 1 is that the reaction temperature is changed to 200° C., and the rest is the same as Example 1.

[0055] Example 6

[0056] The difference from Example 1 is that the reaction time is changed to 20 h, and the rest is the same as Example 1.

[0057] Example 7

[0058] The difference from Example 1 is that the reaction time is changed to 28 h, and the rest is the same as Example 1.

[0059] Comparative Example 1

[0060] The difference from Example 1 is that NCFF foam is replaced by NCF foam, and the rest is the same as Example 1 to obtain NiCoSe x / NCF catalyst.

[0061] Comparative Example 2

[0062] The difference from Example 1 is that NCFF foam is replaced with FCF foam, and the rest is the same as Example 1 to obtain FeCoSe x / FCF catalyst.

[0063] Comparative Example 3

[0064] The difference from Example 1 is that commercial precious metals are loaded on the NCFF foam. The specific loading method is: ultrasonically disperse Pt / C in ethanol and add perfluorosulfonic acid, drop it on the surface of NCFF and dry it to obtain Pt / C-NCFF catalyst.

[0065] Testing and result analysis

[0066] The catalysts prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were subjected to the following tests.

[0067] 1. Test method description

[0068] 1. Material Characterization

[0069] The morphology and surface characteristics of the catalysts were observed in detail by field emission scanning electron microscopy (SEM, JSM-6700F, JEOL, Japan). The crystal structure and interplanar distance of the samples were studied by transmission electron microscopy (TEM, JSM 2100, JEOL, Japan), while the elemental composition and content were analyzed by energy dispersive spectroscopy (EDX). X-ray diffraction (XRD, Thermo Fisher Scientific, USA) and X-ray photoelectron spectroscopy (XPS, K-Alpha, USA) were used to detect the crystal phase and elemental state of the samples, respectively.

[0070] 2. Electrocatalytic evaluation

[0071] The electrochemical properties were measured in 1.0 M KOH solution (pH = 14) and room temperature 25 ° C, using a CHI 660E electrochemical workstation. The experimental configuration includes a three-electrode system, in which the catalyst sample is used as the working electrode, the carbon rod is used as the counter electrode, and Hg / HgO is used as the reference electrode. It is noted that the size of the test sample is 0.25 cm 2 , and the working electrode was activated by scanning with cyclic voltammetry (CV), and the scan rate was set to 1 mV / s. In addition, the current-voltage curve was recorded by linear sweep voltammetry (LSV). The electrochemical impedance spectroscopy (EIS) was measured in the frequency range of 0.02 Hz to 100 kHz, the AC voltage amplitude was set to 5 mV, and the measurements were performed at different potentials. The potentials in all experimental data were corrected relative to the reversible hydrogen electrode (RHE) according to the Nernst equation, and its expression is: EvsRHE =E vsHg / HgO +0.095+0.059pH. For the experimental data, 100% internal resistance (iR) compensation was performed, and the corrected potential expression is E Corrected =E Raw -IRs, where E Corrected is the corrected potential, E Raw is the original measured potential, and Rs is the solution resistance. The calculation of the double layer capacitance (Cdl) is used to estimate the electrochemically active surface area (ECSA). The transition frequency (TOF) of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is calculated based on the TOF HER =jS / 2nF and TOF OER = jS / 4nF, where S, j, n and F represent the electrode surface area, current density, amount of substance and Faraday constant (96485C mol -1 ). By comparing Pt / C and RuO with the same catalyst mass loading 2 HER and OER performance of powder coated samples. Gas emission measurements were performed every 10 minutes to determine the production of hydrogen and oxygen. Chronoamperometric curves were used to evaluate the HER or OER stability of the catalysts at different current densities. Finally, the catalyst samples were assembled into a two-electrode system to evaluate their overall water splitting performance, and their stability was studied by measuring It curves at constant voltage.

[0072] 3. Theoretical calculation

[0073] All calculations were performed within the framework of density functional theory using the projector augmented plane wave method as implemented in VASP (Reference: Kresse, G.; Joubert, D. From ultrasoft pseudopotentials to the projector augmented-wave method. Physical Review B 1999, 59, 1758-177.). The generalized gradient approximation proposed by Perdew, Burke and Ernzerhof (Reference: Heyd, J.; Scuseria, GE; Ernzerhof, M. Hybrid Functionals Based on a Screened Coulomb Potential J. Chem. Phys. 2003, 118, 8207.) was chosen as a hybrid density functional screened by the exchange-correlation potential (Reference: Perdew, JP; Burke, K.; Ernzerhof, M. Generalized gradient approximation made simple. Physical Review Letters 1996, 77, 3865-3868.). The van der Waals interaction was described by the DFT-D3 method (reference: Grimme, S.; Antony, J.; Ehrlich, S. and Krieg, H. A consistent and accurateab initio parametrization of density functional dispersion correction (DFT-D) for the 94elements H-Pu. Journal of Chemical Physics 2010, 132, 154104.). The plane wave cutoff energy was set to 400 eV. In the iterative solution of the Kohn-Sham equation, the energy criterion was set to 10-4 eV. A wave perpendicular to the sheet was added. The vacuum layer is 2x2x 1K to avoid artificial interactions between periodic images. The Brillouin zone integration is performed using a 2x2x 1K grid. All structures are relaxed until the residual forces on the atoms drop to less than The calculation methods of HER and OER are consistent with our previous calculation methods (Reference: Li T, Yu Y, Pei M. Dual-Atom Doping Carbon Materials as Highly Efficient Electrocatalysts for Lithium-Sulfur Batteries: Bimetallic Cooperation Mechanism[J]. The Journal of Physical Chemistry C, 2023, 127(13): 6271-6279.).

[0074] 2. Test Results and Analysis

[0075] 1. Structure and characterization

[0076] In order to determine the most suitable growth conditions for multiphase selenides with high water electrolysis activity, we controlled three variable parameters: selenium powder content in the reaction solution, temperature and time of the hydrothermal reaction, prepared the corresponding samples, and then tested their LSV polarization curves of HER and OER reactions.

[0077] according to Figure 2 The results show that when 0.08 g of selenium powder is uniformly dispersed in the reaction solution, the sample exhibits the highest HER and OER activities, indicating that the selenium powder concentration at this time is most suitable for the growth of multiphase selenides.

[0078] And from Figure 3 It can be seen that when the hydrothermal temperature is 180 °C, the prepared sample exhibits the best bifunctional performance, which may be because the selenide forms the most complete morphology and crystal phase at 180 °C.

[0079] Finally, according to Figure 4 The results show that when the reaction time is 24 hours, the sample exhibits the best HER and OER performance, which indicates that at the most suitable selenium powder concentration and reaction temperature, the morphology and crystal structure of the selenide grow to the most suitable form in 24 hours, and continuing the reaction may lead to structural destruction.

[0080] After determining the optimal parameter environment for the selenization reaction, the present invention analyzed the Fe-NiCoSe prepared in Example 1 through XRD patterns. x / NCFF and NiCoSe grown on NCF prepared in Comparative Example 1 without iron x / The specific crystal structure of NCF samples, such as Figure 5 The results shown in the figure show that the crystal structures of the two are basically the same. The peak shape of the spectrum can be indexed to CoSe 2 (JCPDS No.09-0234), CoSe2 (JCPDS No.10-0408), Co 3 Se 4 (JCPDS No.89-2001) and Ni 3 Se 4 (JCPDS No.18-0890). Specifically, the peaks at 34.2°, 51.8°, 63.4°, 72.0° and 76.0° correspond to CoSe 2 The (210), (311), (400), (420) and (332) planes of (JCPDS No. 09-0234) and the four peaks at 30.8°, 34.7°, 36.3° and 47.8° correspond to the CoSe 2 (JCPDS No.10-0408) (110), (111), (012) and (121) planes. 2 Outside, Co 3 Se 4 The (400), (511), (440), (444), (731), (733) and (840) crystal planes of (JCPDS No. 89-2001) can also correspond to the peaks at 35.2°, 46.2°, 50.6°, 63.1°, 70.9°, 76.4° and 85.0° in the spectrum. 3 Se 4 The corresponding peaks of (-112), (202), (013), (-114), (204), (310), (-116), (-125), (008) and (109) of (JCPDS No.18-0890) can be found at 33.2°, 33.7°, 35.6°, 44.8°, 45.3°, 50.7°, 60.4°, 70.0°, 72.0° and 84.4° in the spectrum. The above XRD data show that the nickel-cobalt bimetallic selenide was successfully synthesized. In addition, it can be clearly observed in the XRD peak spectrum that the Fe-NiCoSe synthesized on the trimetallic substrate x The peaks of / NCFF near 33.8°, 45.4°, 51.2° and 84.4° are compared with those of the iron-free sample NiCoSe x / NCF has a slight shift, all deviating to the right by about 0.1°. This also proves that Fe participates in the synthesis of selenide particles and is doped into selenide particles in the form of a single substance or a compound. This doping is also very beneficial to improving its catalytic performance. Figure 6 We can clearly observe that the samples prepared with Fe-Co alloy foam without Ni as substrate are significantly lacking in crystalline Ni 3 Se 4(JCPDS No.18-0890) corresponds to the key main peak of the (-114) plane. However, other peaks still exist and can correspond well to the crystal plane of CoSe2, which also proves that the metal nickel selenide has been successfully synthesized on the surface of NCF or NCFF, so that it can form a heterogeneous interface with the cobalt selenide, thereby significantly improving the activity of the catalyst. Figure 6 As can be seen, the sample made of Fe-Co alloy foam without nickel obviously lacks crystalline Ni 3 Se 4 The key main peak corresponding to the (-114) plane of (JCPDS No.18-0890). However, other peaks still exist and can be well corresponded to CoSe 2 This also proves that the metal nickel selenide was successfully synthesized on the surface of NCF or NCFF, thereby forming a heterogeneous interface with the cobalt selenide and significantly improving the catalyst activity.

[0081] In order to explore and analyze the microscopic morphology and surface crystalline structure of the Fe-NiCoSe prepared in Example 1, SEM and TEM were used to analyze the x / NCFF catalysts were studied in detail. Figure 7 a is Fe-NiCoSe x / The morphology of NCFF under SEM low resolution shows that the foam skeleton of NCFF is covered with uniform and dense particles, with a size of about 3-5μm and an irregular shape with protruding edges and corners. Figure 7 b is a high-resolution SEM image. At a larger magnification, it can be clearly seen that the surface of the particles is densely covered with nanowires with extremely fine diameters and short lengths. These extremely fine and densely distributed nanowires can provide a large reaction area and expose a large number of active sites, thereby greatly improving the Fe-NiCoSe x / NCFF catalytic activity. Figure 7 From the skeleton mapping diagram of c, we can see that Ni, Co, Fe, Se and O are evenly distributed, which means that the generated multi-metal selenide is evenly distributed on the skeleton. Although the amount of Fe is extremely rare, it is also evenly distributed on the foam skeleton. Figure 7 From the low-resolution TEM and elemental energy spectrum in d, it can be found that Ni, Co, Fe, Se and O elements are also evenly distributed in the particle fragments and nanowires observed in SEM. Although Table 1 shows that the iron content is only 0.78%, it can still be explained that the three metals of nickel, cobalt and iron are all involved in the formation of selenide particles.

[0082] Figure 7 e and Figure 7f is a high-resolution TEM image. Clear crystal planes can be seen in both images. The crystal plane spacings of 0.266nm, 0.202nm, and 0.252nm can all be attributed to Ni 3 Se 4 , corresponding to the (202), (-114) and (013) planes, respectively. In addition, the lattice spacings of 0.262nm, 0.190nm and 0.290nm can correspond to CoSe 2 (210), (121) and (110) crystal planes. It is worth noting that from the crystal plane distribution in the figure, it can be clearly seen that Ni 3 Se 4 The (202) crystal plane and CoSe 2 (210) crystal plane, CoSe 2 The (121) crystal plane and Ni 3 Se 4 (013) crystal plane, CoSe 2 The (110) crystal plane and Ni 3 Se 4 The (013) crystal plane of the selenide (Fe-NiCoSe x ) has a very rich heterogeneous interface in the crystal structure. This is extremely beneficial to the performance improvement of the catalyst. In addition, in addition to a large number of crystal faces, many amorphous phases can also be clearly seen in the high-resolution TEM image, indicating that the selenide particles are composed of a crystalline phase and an amorphous phase. Therefore, although no iron crystal phase is found, combined with Figure 7 The mapping diagram in d still shows that the iron element may exist uniformly in the form of single atoms or amorphous selenide in Fe-NiCoSe x In the whole Fe-NiCoSe x This hybrid structure of amorphous and crystalline phases also has a very positive effect on electrocatalytic performance. The results of SEM and TEM together show that the nickel-cobalt-iron trimetallic multi-heterostructure selenide particles covered with extremely fine nanowires have been successfully synthesized on the NCFF surface.

[0083] Table 1

[0084]

[0085] In order to further investigate the Fe-NiCoSe prepared in Example 1 x / The chemical composition and bonding state of the NCFF surface were determined by testing the XPS spectrum of the sample. Figure 8 The XPS spectrum of a Figure 8 bf High-resolution spectra of each element. Figure 8In b, the two peaks at the energy positions of 879.42 eV and 861.77 eV are fitted as two satellite peaks, and the remaining four peaks are attributed to Ni in the metal compound. 2+ (Ni 2p 1 / 2 :873.37eV,Ni 2p 3 / 2 :855.67eV) and Ni 3+ (Ni 2p 1 / 2 :869.97eV,Ni 2p 3 / 2 :852.86eV) Ni 2p 1 / 2 and Ni 2p 3 / 2 Track. Similarly, Figure 8 The high-resolution spectrum of Co2p in c is fitted into six peaks. The satellite peaks corresponding to the two energy positions of 802.48 eV and 785.52 eV are first excluded. The two peaks at the positions of 797.13 eV and 781.20 eV can be attributed to Co 2+ Co 2p 1 / 2 and Co 2p 3 / 2 orbital, and the remaining two peaks at 793.21eV and 778.4eV were assigned to Co 3+ Co 2p 1 / 2 and Co 2p 3 / 2 track. Figure 8 d shows the various chemical states of iron, including the two satellite peaks at 733.23 eV and 716.54 eV, as well as the Fe 3+ Fe 2p 1 / 2 (722.20 eV) and Fe 2p 3 / 2 (713.60 eV) orbital, and Fe 2+ Fe 2p 1 / 2 (719.46 eV) and Fe2p 3 / 2 (711.13 eV) orbital. This indicates that Fe-NiCoSe x During the preparation of the NCFF catalyst, the iron element forms amorphous compounds such as iron selenide or iron oxide, rather than existing only in the form of a single substance, which further proves that the Fe-NiCoSe x / NCFF is a nickel-cobalt-iron trimetallic selenide catalyst that contains a rich heterojunction interface and combines crystalline phases with amorphous phases. In addition, Figure 8 e shows the chemical state of Se element. First, the peak at 58.71 eV is attributed to Se-O bond, and the chemical states of the remaining peaks at 55.39 eV and 54.49 eV are the same as Se 3d 3 / 2 and Se 3d 5 / 2 Tracks can be agreed upon. Figure 8The peaks at 530.00 eV, 530.83 eV and 532.30 eV in f show that Fe-NiCoSe x / The oxygen element in NCFF catalyst exists in three forms: metal-oxygen bond, hydrogen-oxygen bond and adsorbed oxygen.

[0086] 2. Fe-NiCoSe x HER and OER performance of / NCFF catalysts

[0087] Fe-NiCoSe prepared in Example 1 x The electrocatalytic performance of the / NCFF catalyst was tested as a working electrode in a 1M KOH three-electrode system.

[0088] Fig. 9 a is Fe-NiCoSe prepared in Example 1 x / NCFF catalyst, samples prepared when the substrate was changed to FCF and NCF (FeCoSe x / FCF and NiCoSe x / NCF), loaded with commercial precious metal catalyst Pt / C-NCFF, and HER linear sweep voltammograms (LSV) of substrate NCFF and NCF. First of all, it can be clearly found that NCFF has a significant improvement in HER activity compared with the NCF substrate itself, which directly reflects the positive effect of trace Fe element doping on HER performance. On the other hand, the HER activity of the three different substrates after selenization reaction has been significantly improved in both low current density and high current density areas. Fe-NiCoSe x / NCFF and NiCoSe x / NCF only need 36.07mV and 50.07mV overpotential to reach j 10 , compared with the two substrates NCFF (118.53mV) and NCF (159.4mV), it is obvious that the FeCoSe x The LSV curve of the / FCF sample has an obvious reduction peak in the low current density region, so it is impossible to obtain an accurate j 10 Overpotential, which may be attributed to the existence of side reactions in the electrochemical process. 1000 When Fe-NiCoSe x / NCFF,FeCoSe x / FCF and NiCoSe x / NCF only need overpotentials of 328mV, 396mV and 385mV respectively, which is more obvious than NCFF (514mV) and NCF (692mV). This proves that the selenides of nickel, cobalt and iron have a great effect on improving HER performance. x / NCFF performance at each stage of hydrogen evolution reaction (including 100 :193mV,j 500 : 299 mV) is the best, which benefits from the rich heterojunction interface constructed by nickel cobalt selenide and the incorporation of amorphous iron selenide.

[0089] Fig. 9 b The Tafel slope data calculated for each sample are summarized. It should be noted that FeCoSe x / The calculated Tafel slope value of the FCF sample (18.96mV dec -1 ) is much lower than even Fe-NiCoSe x / NCFF, this data is obviously affected by side reactions due to the presence of reduction peaks in their LSV curves, and therefore cannot truly reflect the kinetic rate of the HER process, so it is not included in the comparison. x / NCFF has the lowest Tafel slope value (33.7mV dec -1 ), lower than NiCoSe x / NCF(45.06mV dec -1 ), NCFF(102.98mV dec -1 ) and NCF (142.39mV dec -1 ), even slightly lower than that of commercial precious metal catalyst Pt / C (34.37mV dec -1 ). This indicates that Fe-NiCoSe x The electrochemical reaction kinetics of the HER process in the 1M KOH environment of the NCFF catalyst showed significant advantages, and the process followed the Volmer-Heyrovsky mechanism.

[0090] In order to further explore the electrochemical reaction kinetics of the HER process of the catalyst samples, their electrochemical impedance spectroscopy (EIS) Nyquist plots ( Fig. 9 c). Fe-NiCoSe x / NCFF has an Rct value of 2.5Ω, which is higher than NiCoSe x / NCF(2.79Ω),FeCoSe x / FCF (2.88Ω), and even Pt / C (3.98Ω) are slightly better, and are far lower than NCFF (9.35Ω) and NCF (18Ω). Generally speaking, a smaller Rct means stronger metallicity and electron transfer ability, which can also lead to higher hydrogen evolution reaction efficiency. This also shows that the growth of trimetallic selenide self-supporting catalysts doped with iron-doped nickel-cobalt alloy foam is an effective way to prepare high-performance HER catalysts.

[0091] In order to examine the Fe-NiCoSe x The HER stability and durability of the / NCFF samples were first tested by testing the LSV curves of the samples after 10,000 cyclic voltammetry (CV) scans. Fig. 9 d), it can be seen that the activity of the sample has almost no decay after a long period of cyclic scanning, especially in the low current density region, the LSV curve is almost the same as the original one, and there is only a very small change in the high current density region, which reflects the Fe-NiCoSe x / NCFF samples have super durability under long-term cycling current.

[0092] In order to further test the stability of the samples, we tested the 10 , j 100 and j 1000 The chronoamperometric curve under Fig. 9 As shown in the three-segment step curve in e, the sample 10 After a long-term constant voltage HER reaction test of 50 h, the current density even increased by 14.8% and the 1000 After 20 h, the increase was 19.6%, which may be due to the activation of active materials under current, thus exposing more active areas. 100 Although it decays slightly, the decay rate is only about 2%, which fully demonstrates that Fe-NiCoSe x / Extreme durability and stability of NCFF samples.

[0093] In addition, in order to explore the Fe-NiCoSe x To investigate the origin of NCFF stability, we characterized the morphology, phase structure and chemical composition of the samples after It test. Fig.10 The SEM low-resolution and high-resolution images of the samples after the It test are shown. Fig.10 The low-resolution scanning electron microscopy image in a shows that Fe-NiCoSe x After a long period of HER process, the microscopic particle structure of NCFF has basically not changed, and its morphology is similar to that before the reaction ( Figure 7 a) Basically remain the same. Fig.10b Continue to observe the surface structure of the particles at a higher magnification and find that the originally upright nanowires on the surface have collapsed and are attached and cross-linked on the surface of the particles. However, it is obvious that the nanowires still exist and are not destroyed or disappeared in the HER reaction, but have changed from upright to collapsed. It can be seen that the catalyst has not changed much in microstructure due to the long-term HER process, which shows the stability of its microscopic physical structure. In addition, the XRD spectrum ( Fig.11 )Analyze the crystal structure of the sample after It, and it can be found that Fe-NiCoSe x The main peaks corresponding to all crystalline phases and their crystal planes of NCFF still exist, only the peak heights of some peaks have changed slightly, which proves that Fe-NiCoSe x The crystal structure of / NCFF is extremely stable in the HER reaction and has basically not changed after 120h of It test.

[0094] Each catalyst was also tested as an OER working electrode. Fig.12 a is the LSV curve. Obviously, Fe-NiCoSe x / NCFF exhibited the best OER activity (j 10 :210mV,j 1000 :345mV), although in the low current region compared with the commercial noble metal catalyst RuO 2 (j 10 :137mV) is still insufficient, but it has better performance at high current density. It is worth noting that the tri-metal foam NCFF doped with trace Fe also shows significantly better activity than NCF in OER, which shows that the incorporation of Fe is extremely beneficial for both OER and HER processes. The three selenized samples all showed significant activity improvement in OER again, which shows that transition metal selenides (TMSes) have great potential for application in both water electrolysis reactions. Fig.12 b shows the Fe-NiCoSe x / NCFF has the lowest Tafel slope (55.92mV dec -1 ), compared with FeCoSe x / FCF(63.21mV dec -1 ), NiCoSe x / NCF(74.13mV dec -1 ) and RuO 2 / NCFF(125.28mV dec -1 ) have advantages, far exceeding the substrate NCFF (90.57mV dec -1 ) and NCF (126.29mV dec -1), which shows that Fe-NiCoSe x / NCFF has a fast kinetic reaction in the OER process. In addition, Fig.12 c shows that the extremely low Rct (1.26Ω) makes Fe-NiCoSe x / NCFF has the ability to quickly transfer electrons, which is more conducive to the oxygen evolution process. Other samples such as FeCoSe x / FCF(1.56Ω),NiCoSe x / NCF(1.44Ω) and RuO 2 / NCFF(3.3Ω) is slightly worse.

[0095] In order to explore the Fe-NiCoSe x To determine whether the advantages of the NCFF catalyst at high current density in the OER reaction can be maintained stably for a long time, we tested its LSV curve after 10,000 voltammetric cycles (CV) scans ( Fig.12 d), the data show that its activity has only been slightly attenuated, j 1000 The overpotential of 359 mV at the time of cycling was only 14 mV higher than that before cycling. x Constant voltage chronoamperometry curve of NCFF in high current density region ( Fig.12 e) Under the condition of long-term high current density oxygen evolution reaction for 25h, the It curve measured fluctuates, but there is no obvious attenuation overall, which proves that Fe-NiCoSe x / Excellent durability of NCFF over the OER process.

[0096] In order to investigate the potential factors that contribute to the superior durability of the samples in the OER reaction, we also characterized the morphology and structure of the samples after the It test. Fig.13 a It can be observed that the long-term oxygen evolution reaction does not change the micron-level morphology of the catalyst surface, and the selenide particles are still evenly and densely distributed on the foam skeleton. Fig.13 b) The obvious nanowire morphology is no longer visible on the surface of the selenide, but is replaced by a honeycomb morphology similar to that formed by cross-linking of nanosheets. This morphology also exposes a large number of active sites and reaction areas, thus retaining the OER activity of the catalyst to a great extent.

[0097] pass Fig.14 It can be observed from the XRD spectrum that after a long period of OER reaction, the peak heights of many peaks change, but the peaks corresponding to the key crystal planes of all major crystal phases still exist, and some peaks are even more obvious. This means that although the surface structure of the catalyst has some changes during the OER process, the crystal phase is not destroyed. While some crystal planes are reduced, some crystal planes are more exposed, such as Ni3 Se 4 The peak height corresponding to the (-114) crystal plane of (JCPDS No.18-0890) increases significantly, which also means that more heterogeneous interfaces can be retained, so there is no obvious activity loss in the catalyst performance.

[0098] The above electrochemical performance test data show that Fe-NiCoSe x / NCFF catalyst has excellent performance in both HER and OER. Fig.15 The double layer capacitance (Cdl) value was found in Fe-NiCoSe x The Cdl value of NCFF is 61.58mF cm -2 , much higher than that of NiCoSe without Fe doping x / NCF(46.08mF cm -2 ) and NCFF substrate (12.34 mF cm -2 ), and then the ECSA value (electrochemically active specific surface area) of each sample can be calculated, which are Fe-NiCoSe x / NCFF: 1529.5cm -1 ECSA ,NiCoSe x / NCF: 1152cm -1 ECSA , NCFF:246.8cm -1 ECSA The large electrochemical active area provides a large number of reactive sites and also supports the Fe-NiCoSe x / NCFF catalyst has high performance in two water electrolysis reactions.

[0099] 3. DFT calculation

[0100] In order to further clarify the Fe-NiCoSe x The performance of selenide crystals on the surface of / NCFF catalyst in HER and OER processes was analyzed by DFT calculation, and the crystal phase and the formed heterogeneous structure determined based on XRD and TEM results were analyzed. Fig.16 The main highly active crystal facets of CoSe established by the VASP computational package are shown. 2 (210), Ni 3 Se 4 (202) and CoSe 2 (210)-Ni 3 Se 4 (202)Atomic model of heterojunction.

[0101] Since the density of states (DOS) is the projection value of the energy band on the vertical axis, Fig.17 The DOS diagram shown in can be used to quantify the CoSe 2 (210), Ni 3 Se 4 (202) and CoSe 2 (210)-Ni 3 Se 4 (202) The relationship between the heterojunction and HER activity. It is obvious that all three exceed the Fermi level in the figure, which reflects the inherent metallic properties of the three, such as low resistance. 2 (210)-Ni 3 Se 4 (202) The heterojunction obviously presents a larger DOS value, and the high state density reflects that the construction of the heterojunction interface increases the electron density, which is more conducive to the HER process. It can be seen that the heterojunction can significantly increase the concentration of free electrons in both the spin-down and spin-up states, which is most likely the main factor in reducing the binding strength of the catalyst surface to intermediate substances such as H*, OH*, O*, and OOH* during the electrocatalytic process.

[0102] Hydrogen adsorption free energy (ΔGH*) is an important parameter for evaluating electrocatalytic activity. Ideally, |ΔGH*| should be close to 0 during the HER process. Fig.18 CoSe can be seen in 2 (210)-Ni 3 Se 4 The ΔGH* value of the (202) heterojunction is -0.384 eV, which is much lower than that of two monolayer crystalline CoSe 2 (210) of -0.624 eV and Ni 3 Se 4 (202) is -1.386 eV. This indicates that CoSe 2 (210)-Ni 3 Se 4 (202) Heterojunction adsorption of H during HER + The energy barrier is extremely low and the hydrogen release efficiency is extremely high. Fig.19 The energy changes of the four stages in the OER reaction are shown. 3 Se 4 (202) and CoSe 2 (210)-Ni 3 Se 4 (202) The rate-determining step of the heterojunction is the second step of generating O*, while for CoSe 2 (210), the decisive process is affected by the third step of generating OOH*. 2 (210)-Ni3 Se 4 (202) The energy barrier of the heterojunction (ΔG 1st :0.243eV, ΔG 2nd :0.376eV) is much smaller than CoSe 2 (210)(ΔG 2nd :0.661eV,ΔG 3rd :1.162eV) and Ni 3 Se 4 (202)(ΔG 2nd :1.168eV, ΔG 3rd :0.213eV) phase energy barrier. This data shows that CoSe 2 (210)-Ni 3 Se 4 (202) The collective effect brought by the heterojunction significantly optimizes the energy barrier required for the OER process, which is particularly evident in the process of OH* to O* conversion and O* to OOH* generation.

[0103] Based on the theoretical calculation results and experimental characterization and test data, it can be found that the dual-phase heterojunction CoSe 2 -Ni 3 Se 4 The free electron concentration is significantly increased, and the energy barriers required for the HER and OER processes are significantly reduced, so both can be driven at lower overpotentials.

[0104] The results of electrochemical tests show that Fe-NiCoSe x / NCFF has excellent activity and stability for both HER and OER. The reasons are summarized as follows through analysis of various characterization test results:

[0105] (1)Fe-NiCoSe x The uniformly dense distribution of micron-sized selenide particles on the microscopic morphology of NCFF and the dense nanowires on its surface provide it with a huge reaction area and extremely rich active sites. The calculated NCFF has a surface area of ​​1529.5 cm -1 ECSA The huge ECSA value also shows that it has a large electrochemically active specific surface area. And its microstructure is not destroyed under long-term high current density HER and OER, which provides it with strong electrocatalytic stability.

[0106] (2) The addition of trace Fe elements causes the catalyst to grow into a richer selenide structure during the selenization process. XPS and TEM results show that the nickel, cobalt and iron metals form micron-sized particles that integrate crystalline and amorphous phases. This is extremely beneficial for improving electrochemical performance.

[0107] (3)Fe-NiCoSe x The extremely low Tafel value of the NCFF catalyst supports its rapid electrochemical kinetic reaction. In addition, the low Rct value indicates its inherent metallic properties, which is conducive to accelerating the transfer of electrons from the electrode to the electrolyte, thereby providing a more efficient electrocatalytic reaction process.

[0108] (4) DFT calculation results show that the dual-phase heterostructure CoSe 2 (210)-Ni 3 Se 4 The high electron density and strong adsorption capacity of (202) for reaction intermediates also indicate that it can adsorb H + As well as the energy barriers of the decisive steps in the OER process are extremely low.

[0109] In summary, Fe-NiCoSex / NCFF prepared by a simple one-step process exhibits excellent HER and OER activities, which are superior to most reported transition metal-based catalysts. The catalyst has uniformly dense micron-sized selenide particles and dense nanowires on its surface, which provide it with a huge reaction surface area and abundant active sites. In addition, XPS and TEM results show that the catalyst is composed of three metals, nickel, cobalt, and iron, forming micron-sized particles that integrate crystalline and amorphous phases, further improving its electrochemical performance. DET results reveal that the CoSe2(210)-Ni3Se4(202) heterojunction shows a higher state density, indicating that the formation of a heterogeneous interface increases the electron density, which is more conducive to the HER and OER processes. More importantly, at high current density, Fe-NiCoSex / NCFF exhibits excellent stability in both HER and OER reactions, which is of great significance for the development of transition metal-based catalysts towards commercial applications.

[0110] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A Fe-NiCoSe x / A method for preparing a NCFF catalyst, characterized in that: The following steps are involved: Wash the NCFF foam and dry it; Selenium powder, hydrazine hydrate and deionized water were mixed evenly, added to the NCFF foam, and reacted at a certain temperature to obtain Fe-NiCoSe x / NCFF catalyst.

2. A Fe-NiCoSe according to claim 1 x / A method for preparing a NCFF catalyst, characterized in that: The NCFF foam cleaning method comprises: ultrasonically cleaning the NCFF foam in acetone solvent and HCl solution for 5 to 15 minutes respectively, and then taking out the NCFF and washing the surface of the NCFF with anhydrous ethanol and deionized water in turn.

3. A Fe-NiCoSe according to claim 1 x / A method for preparing a NCFF catalyst, characterized in that: The NCFF foam drying method comprises: drying the cleaned NCFF in a drying oven at 45 to 55° C. for 10 to 20 minutes.

4. A Fe-NiCoSe according to claim 1 x / A method for preparing a NCFF catalyst, characterized in that: The ratio of the selenium powder, hydrazine hydrate and deionized water is 0.06-0.1 g: 1.5-2.5 ml: 18-22 ml.

5. A Fe-NiCoSe according to claim 1 x / A method for preparing a NCFF catalyst, characterized in that: The ratio of the selenium powder, hydrazine hydrate and deionized water is 0.07-0.09 g: 1.8-2.2 ml: 19-21 ml.

6. A Fe-NiCoSe according to claim 1 x / A method for preparing a NCFF catalyst, characterized in that: The ratio of the selenium powder, hydrazine hydrate and deionized water is 0.08 g: 2 ml: 20 ml.

7. A Fe-NiCoSe according to claim 1 x / A method for preparing a NCFF catalyst, characterized in that: React in a forced air drying oven at 160-200°C for 20-28 hours.

8. A Fe-NiCoSe according to claim 1 x / A method for preparing a NCFF catalyst, characterized in that: The mixture was reacted at 180°C in a forced air drying oven for 24 h.

9. A Fe-NiCoSe according to claim 1 x / A method for preparing a NCFF catalyst, characterized in that: The size of the NCFF foam is 0.5-1.5 cm×0.5-1.5 cm.

10. Fe-NiCoSe obtained by the preparation method according to any one of claims 1 to 9 x / NCFF catalyst.

Citation Information

Patent Citations

  • Foamed nickel-loaded iron-cobalt-nickel metal nano-catalyst and preparation method and application thereof

    CN111495417A

  • Ferrocobalt selenide and preparation method thereof

    CN111825063A

  • Preparation method of bimetallic selenide Ni&lt;x&gt; Co&lt;1-x&gt;Se composite material

    CN113808855A

  • Nickel iron diselenide compound, process for the preparation thereof and its use as a catalyst for oxygen evolution reaction

    WO2018015891A1

Cited By

  • Iron-rich transition metal selenide electrolyzed water catalyst and preparation method thereof

    CN120291135A

  • Iron-rich transition metal selenide catalysts for water electrolysis and methods of making the same

    CN120291135B